ANALISIS PERSEPSI MAHASISWA TERHADAP KUALITAS PELAYANAN UNIVERSITAS BUANA PERJUANGAN KARAWANG ( PROGRAM STUDI MANAJEMEN) - Suroso . (BUANA ILMU, 2017)
Abstract The purpose of thi research analyze students’perceptions toward service quality Buana Perjuangan Karawang University Program Management. Program Management received most students than the other study programs. The first class of the year 2015/2016 registered about 241 students. However along the time, there are some students who have resigned or moved to another campus. The students reduction is due to dissatisfaction with the services UBP Karawang or other factors. Therefore, the research is needed with analyzing the quality of service management UBP Karawang management program. Quality of service is good that to have suitability between the expectations with student assessment that based on the perception. The research method used descriptive qualitative method by using data analysis techniques Importance-Performance Analysis (Jonh A. Martila and John C. James, 1977) or importance and performance analysis or customer perception. The technique of collecting data using interviews and questionaires with random sampling techniques and slovin with 7,5% rate. Population is 225 and sample is 100 responden. The conclusion of research that the perception of students toward service quality Buana Perjuangan Karawang University (program management) is good enough. Because of there is a suistability between the expections with perception of students. Key: Perception Students, Service Quality